Heterogeneity in colorectal cancer incidence among people recommended 3-yearly surveillance post-polypectomy: a validation study - Robbins, Emma C.; Wooldrage, Kate; Stenson, Iain; Pack, Kevin; Duffy, Stephen; Weller, David; Levin, Theodore; Conell, Carol; Wright, Suzanne; Nickerson, Claire; Martin, Jessica; Cross, Amanda J. (Endoscopy, 2020)
Background Colonoscopy surveillance is recommended for patients at increased risk of colorectal cancer (CRC) following adenoma removal. Low-, intermediate-, and high-risk groups are defined by baseline adenoma characteristics. We previously examined intermediate-risk patients from hospital data and identified a higher-risk subgroup who benefited from surveillance and a lower-risk subgroup who may not require surveillance. This study explored whether these findings apply in individuals undergoing CRC screening. Methods This retrospective study used data from the UK Flexible Sigmoidoscopy Screening Trial (UKFSST), English CRC screening pilot (ECP), and US Kaiser Permanente CRC prevention program (KPCP). Screening participants (50 – 74 years) classified as intermediate-risk at baseline colonoscopy were included. CRC data were available through 2006 (KPCP) or 2014 (UKFSST, ECP). Lower- and higher-risk subgroups were defined using our previously identified baseline risk factors: higher-risk participants had incomplete colonoscopies, poor bowel preparation, adenomas ≥ 20 mm or with high-grade dysplasia, or proximal polyps. We compared CRC incidence in these subgroups and in the presence vs. absence of surveillance using Cox regression.Results Of 2291 intermediate-risk participants, 45 % were classified as higher risk. Median follow-up was 11.8 years. CRC incidence was higher in the higher-risk than lower-risk subgroup (hazard ratio [HR] 2.08, 95 % confidence interval [CI] 1.07 – 4.06). Surveillance reduced CRC incidence in higher-risk participants (HR 0.35, 95 %CI 0.14 – 0.86) but not statistically significantly so in lower-risk participants (HR 0.41, 95 %CI 0.12 – 1.38).Conclusion As previously demonstrated for hospital patients, screening participants classified as intermediate risk comprised two risk subgroups. Surveillance clearly benefited the higher-risk subgroup.